Zika virus replicates in adult human brain tissue and impairs synapses and memory in mice - Figueiredo, Claudia P. (Nat Commun, 2019)
Neurological complications affecting the central nervous system have been reported in adult patients infected by Zika virus (ZIKV) but the underlying mechanisms remain unknown. Here, we report that ZIKV replicates in human and mouse adult brain tissue, targeting mature neurons. ZIKV preferentially targets memory-related brain regions, inhibits hippocampal long-term potentiation and induces memory impairment in adult mice. TNF-α upregulation, microgliosis and upregulation of complement system proteins, C1q and C3, are induced by ZIKV infection. Microglia are found to engulf hippocampal presynaptic terminals during acute infection. Neutralization of TNF-α signaling, blockage of microglial activation or of C1q/C3 prevent synapse and memory impairment in ZIKV-infected mice. Results suggest that ZIKV induces synapse and memory dysfunction via aberrant activation of TNF-α, microglia and complement. Our findings establish a mechanism by which ZIKV affects the adult brain, and point to the need of evaluating cognitive deficits as a potential comorbidity in ZIKV-infected adults.